Measurement of prospective memory in Spanish speakers - Cadavid, Laura; Camuy, Alicia; Velez, Valerie; Raskin, Sarah (Frontiers in Human Neuroscience, 2023)
This study aimed to provide preliminary evidence on the psychometric properties of a measure of prospective memory in Spanish speakers, the Memory for Intentions Test (MIST) Spanish translation. In addition, this study investigated whether acculturation influenced performance on the MIST. Finally, we measured other cognitive factors that might be impacting the relationship between culture and prospective memory performance. These factors were working memory, autobiographical memory, and episodic future thought. Overall, the psychometric properties of the Spanish MIST appear to be similar to the English language MIST, but our sample size was too small to allow for the creation of a normative database. The MIST recognition item was significantly related to years of education and years of speaking either Spanish or English, suggesting a need to investigate ways to improve the test to eliminate these effects. In addition, acculturation was related to the measure of episodic future thought.